Relationship of The Sales Promotion Exposure, Marketing Communication Competence, Brand Image Toward Client’s Loyalty of Trax FM Semarang - Annisa Nabiha Firdausi Nuzula; Dra. Sri Widowati Herieningsih, MS (Interaksi Online, 2016)
Radio is a media of information and business which can provide up to date information to public by relying on its rapidity, radio can be the media that is still highly considered in the promotional activities of client companies which do cooperate with some radios. Trax FM Semarang is one of regional radio that is still highly considered by clients to become their media partners. In the business relationship, there are many factors that can make some strong relation of the partnership between two parties. This study aims to find out the relation between of the sales promotion exposures, marketing communication competence, and brand image of client’s loyalty Trax FM Radio Semarang. In order to solve the problems, used some theories, such as Behavioural Learning theory, Speech Act theory, Communication Competence theory, and Cognitive Learning theory. The objects of the study were companies who work with Trax FM Semarang at least for 2 times of partnership within one year. The amount of respondents was about 30 companies who were taken by using the technique of non-probability sampling. The data were analyzed by using proper test and classic assumption test, and then followed by pearson’s correlation analysis with the help of SPSS application program V.20.0. The study resulted in that from 3 (three) variables of X, 2 (two) of them received positive value, that was marketing communication competence and brand image. Respondents appraised that the Trax FM Semarang has competent marketing in their field, and Trax FM Semarang is a radio that has a pretty good brand image. However it is not certain that is positively related to client’s loyalty of Trax FM Semarang. After did the hypothesis test by the method of pearson’s correlation test, it resulted in that the first hypothesis of this study showed there is no relation between sales promotion exposure variable (X1) to the client’s loyalty of Trax FM Semarang (Y). Then, the second hypothesis test (X2) showed that marketing communication competence variable has no relation to client loyalty of Trax FM Semarang. Moreover, the third hypothesis test resulted that brand image variable (X3) was not related to client’s loyalty of Trax FM Semarang (Y).